Three-Dimensional Pseudo-Continuous Arterial Spin Labeling Parameters Distinguish Pediatric Medulloblastoma and Pilocytic Astrocytoma - Duc, Nguyen Minh (Frontiers in Pediatrics, 2021)
Introduction: Arterial Spin Labeling (ASL), a perfusion assessment without using gadolinium-based contrast agents, is outstandingly advantageous for pediatric patients. The differentiation of medulloblastomas from pilocytic astrocytomas in children plays a significant role in determining treatment strategies and prognosis. This study aimed to assess the use of ASL parameters during the differentiation between pediatric medulloblastoma and pilocytic astrocytoma. Methods: The institutional review board of Children’s Hospital 2 approved this prospective study. The brain magnetic resonance imaging (MRI) protocol, including axial three-dimensional (3D) pseudo-continuous ASL, was evaluated in 33 patients, who were divided into a medulloblastoma group (n = 25) and a pilocytic astrocytoma group (n = 8). The quantified region of interest (ROI) values for the tumors and the tumor to parenchyma ratios were collected and compared between the two groups. Receiver operating characteristic (ROC) curve analysis and the Youden index were utilized to identify the best cut-off, sensitivity, specificity, and area under the curve (AUC) values for significant ASL parameters. Results: The cerebral blood flow (CBF) and the ratio between the CBF of the tumor relative to that of the parenchyma (rCBF) values for medulloblastomas were significantly higher than those for pilocytic astrocytomas (p < 0.05). A cut-off value of 0.51 for rCBF was able to discriminate between medulloblastoma and pilocytic astrocytoma, generating a sensitivity of 88%, a specificity of 75%, and an AUC of 83.5%. Conclusion: The rCBF measurement, obtained during MRI with 3D pseudo-continuous ASL, plays a supplementary role in the differentiation of medulloblastoma from pilocytic astrocytoma.